Assessment of the Outcomes of Identity in the Merdeka Curriculum at Witri Kindergarten Bengkuluu - Oktariani, Dwi; Nirwana, Evi Selva (Jurnal Ilmiah Wahana Pendidikan, 2024)
Early Childhood Education (ECED), Merdeka Curriculum, Self-Assessment, Project-Based Learning, Creativity Development, Character Values, Teaching Flexibility, Socio-Emotional Development, TK Witri Bengkulu, Qualitative Method, Literature Study, Document Analysis, Self-Awareness Development, Responsibility, Positive Social Interaction.Early childhood education (ECED) plays an important role in the formation of children's character and identity. This article examines the implementation of Merdeka Curriculum in Witri Kindergarten Bengkulu, which emphasizes project-based learning, creativity, and character values. This research aims to explore the process and impact of early childhood identity assessment in the context of Merdeka Curriculum. Using qualitative methods, the research involved a literature study and document analysis, including child development reports and observation notes. The results show that identity assessment has a positive impact on early childhood learning outcomes. The majority of children show good development in recognizing and expressing emotions, emotional management strategies, initiating and participating in games, resolving conflicts, wanting to try new things, and positive behavior towards the environment. The implementation of Merdeka Curriculum at Witri Kindergarten Bengkulu has succeeded in providing the flexibility needed by teachers to adjust teaching materials and methods to the needs and potential of children, thus supporting the development of their identity optimally. This research provides valuable insights for educators, researchers, and policy makers in an effort to improve the quality of early childhood education in Indonesia. The findings are expected to serve as a model for other schools in developing character and early childhood social-emotional skills through Merdeka Curriculum